Notice of Retraction: Bilateral synchronous percutaneous nephrolithotomy - Paksi Satyagraha; Besut Daryanto; Prasetyo Nugroho (Brawijaya Journal of Urology, 2022)
This article has been retracted by the publisher. ----------------------------------------------------------------------- This article has been retracted at the request of the Authors. The editors and authors have jointly made the decision to retract the paper. Reasonable effort should be made to remove references to this paper. ----------------------------------------------------------------------- Introduction. Bilateral synchronous Percutaneous Nephrolithotomy (PCNL) begins to be considered as an effective therapy as the staged PCNL for bilateral kidney stone treatment, but it remains to be an challenging procedure. Especially on bilateral obstruction patients that already developed severe hydronephrosis.Case. We present a case of a 49 years old male with flank pain on both sides continuously. From non- contrast abdominalCT-scan showed bilateral pyelum stone and bilateral severe hydronephrosis. From laboratory findings, the creatinine serum was 1,5 mg/dL and ureum serum was level 69,8 mg/dL. We performed bilateral synchronous PCNL in a prone position, and stone fragmentation with a pneumatic lithotripter. The operation lasted for about 2 hours with minimal amount of bleeding. After 5 months of follow-up, he already has no stone with normal ureum-creatinine level (0,77mg/dL; 43,7 mg/dL) and did not have any complaint.Conclusion. Bilateral synchronous PCNL is a safe choice to be done in order to treat bilateral pyelum stone, it can decrease length of stay, total cost therapy, and morbidity of the patient.